Voronoi-Cluster Multi-Resolution Hierarchical Codebook Design for Cell-Free Integrated Sensing and Communication Systems - Cao, Yu; Yu, Qi-Yue; Guo, Ji-Chong; Cheng, Julian (IEEE transactions on communications, 2024)
Cell-free integrated sensing and communication (ISAC) offers simultaneous high-quality communication and robust target sensing, boasting superior spectral efficiency. This approach has emerged as a crucial technique in meeting the demanding requirements of 6G systems. For such a system, we investigate Voronoi-cluster multi-resolution assemblages, which involves the creation of a multi-resolution hierarchical codebook designed to support robust channel estimation and accurate latency estimation. Compared with the classical channel estimation method, the proposed scheme achieves a balance between search efficiency and detection accuracy. Leveraging on the benefits of the cell-free structure, we also propose a joint correlation multiple targets sensing algorithm to acquire the round-trip latencies of multiple targets. Moreover, we evaluate the performances of normalized mean square error, detection rate and latency estimation rate. Simulation results demonstrate that the proposed cell-free ISAC architecture provides superior detection performances than the classical centralized ISAC counterpart.